GLOBALIZATION AND ITS IMPACT ON THE POPULARITY OF ELITE BASKETBALL IN IRAQ, A STUDY İN THE LIGHT OF ACTUAL TRENDS AND PROBLEMS IN TRAINING - Dr. Mustafa Asaad Munshed (American Journals Publishing, 2023)
The research aims to identify training problems in the field of basketball for the elite class in the Iraqi league, study the impact of globalization on the popularity of this game, and make recommendations in the light of the research results to help overcome training problems, enhance the positive effects of globalization and avoid the negative effects.The final research sample reached (30) administrators in the Iraqi Basketball Association, and to achieve the research objectives, the researcher used the descriptive approach due to its suitability to the nature of the research, and the variables were represented by gender and the number of years of administrative work, while the questionnaire was adopted as a research tool.The research results revealed a set of points, most notably:• The most prominent training problems in the game of basketball revolve around focusing on physical ability exercises, relying on theoretical explanation, and not reviewing the mistakes of the previous match.• The most prominent effects of globalization on elite basketball were the widespread use of stimulants, the increase in mass violence and riots on the stands.• The agreement of the respondents about the problems of training in the game of basketball according to the variable of sex, and their differences about it according to the variable of the number of years of sports work.• The respondents agreed about the effects of globalization on the popularity of the game according to the search variables.In light of this, the researcher suggests emphasizing the integration and cooperation between the team members, balancing between theoretical and practical work, in order to achieve the best results, and increasing the time allotted for explaining training plans during training periods, and working on them continuously and not just a day or two before the match, and emphasizing mutual respect. between the members of the team, the coaching staff and the responsible administrative staff, creating an atmosphere of love and affection among them, focusing on the positive side of globalization, and working as much as possible to avoid its negatives.
Keywords: basketball, actual problems, training, globalization, elite.